# hi.....i need some help,,,, if any1 izz gd in trignometry,,,,,,,den pls.......................... sinQ (1+tanQ) + cosQ (1+cotQ) = secQ + cosecQ cosQ / 1-tanQ  - sin2Q / cosQ-sinQ   = sinQ + cosQ secQ (1-sinQ) (secQ + tanQ) = 1 2sec2Q - sec4Q - 2cosec2Q + cosec4Q = cot4Q - tan4Q

2.  LHS =  CosQ / 1- tanQ - sin2Q / CosQ - SinQ

=  cosQ / 1 - (sinQ/CosQ)  - Sin2Q / CosQ - SinQ

=  cosQ / (cosQ-sinQ/CosQ)  - Sin2Q / CosQ - SinQ

=  Cos2Q / CosQ - SinQ - Sin2Q / CosQ - SinQ

=  Cos2Q  - Sin2Q / CosQ - SinQ   ( by appliying formula   a2 - b= (a+b)(a-b) )

= (cosQ + sinQ)(CosQ - SinQ)/ CosQ - SinQ

=  cut out both d values...

= cosQ + sinQ

= RHS

• 3

3.  LHS = secQ(1 - sinQ)(secQ + tanQ)

=  ( SecQ - SecQ*sinQ)(secQ + tanQ)

=  ( SecQ - 1/cosQ*sinQ)(secQ + tanQ)

=  ( SecQ - tanQ)(secQ + tanQ)  applying identity (a+b)(a-b) = a2 - b

(sec2Q - tan2Q)

=  1

=  RHS

• 3

Baki 2 i'ill tell u tomorrow....abi i have to leave.........

• 1

thanxxx a lot sangam,.,,,,.,..,,,!!!.,,

• 1

1.LHS=sinQ(1+sinQ/cos Q) +cosQ (1+cosQ/sinQ)

= sinQ+ sin2Q/ cos Q+cos Q+ cos 2Q)/sinQ

=sin Q +cos Q +(1-cos2Q)/cosQ+ (1-sin 2Q)/sin Q putting sin2Q= 1-cos2Q

=sin Q+cos Q+secQ -cosQ +cosecQ - sinQ

= secQ+cosec Q= RHS

• 1

4.LHS= 2(sec2Q -cosec2Q) - (sec4Q -cosec4Q)

=2(sec2Q - cosec2Q) - (sec2Q -cosec2Q)(sec2Q +cosec2Q)

=(sec2Q - cosec2Q)(2- sec2Q - cosec2Q)

=(tan2Q +1 - cot2Q -1)(-1)(sec2Q -1 +cosec2Q -1)  putting tan2Q +1= sec2Q ,cot2Q +1= cosec2Q

=(cot2Q -tan2Q)(tan 2Q +cot2Q)

= cot4Q- tan4Q=rhs

• 3

thanku,.,,,...,,. these were really important 4 me,.,,,,,, thumbs up 2 both of u,.,,,,!!!...:)

• 1

LHS=SINQ (1+TANQ)=COSQ (1+COTQ)

=SINQ+SINQ/TANQ +COSQ+ COSQ*COTQ

=SINQ+ SINQ*SINQ/COSQ+ COSQ+COSQ*COSQ/SINQ

=(SIN3Q+COS3Q+ SIN2Q*COSQ+ COS2Q*SINQ) /SINQ*COSQ

={(SINQ+COSQ) (SIN2Q+COS2Q-SINQ*COSQ) +SINQ*COSQ (SINQ+COSQ)} /SINQ*COSQ

={(SINQ+COSQ) (1-SINQ*COSQ + SINQ*COSQ)} /COSQ*SINQ

=SINQ/SINQ*COSQ +COSQ/COSQ*SINQ

=1/COSQ+ 1/SINQ

=SECQ+ COSECQ

=

=

• 1

thanxxxxx,,,,.......HeY sEe I'm Da FiRsT pErSoN 2 gIvE u A tHuMs Up,,,,,,,!,!,..!..

• 2

prove LHS = RHS(1 + cos q - (sinqsinq)) / (sinq(1+ cosq)) = cotq

• 0
tanq/1-cotq+sinq/1-sinq
• 3
sin2Q/cotQ + COS2/tanQ + 2sinQ *cosQ = 2sec*cosecQ = tanQ + cotQ
• 0
What are you looking for?